Eczane Teknikerliği Temel İlkeleri - Kıran, Bülent; Büyüker, Sultan Mehtap; Arslan, Miray; Yazgan Ekici, Ayşe Nur; Acar Sancar, Aylin; Şar, Sevgi; Tarhan, Nilay; Gür Demircigil, Esra Simten; İlbars, Hilal and Özkaya, Yağmur and Erdoğan, Özlem and Aksu, Neşe Buket and Hussein, Hasan Ali and Eren, Rumeysa and Ulutaş Deniz, Elif and Gülpınar, Gizem and Coşkun, Ronayı and Çağ, Ayşenur and Sözen Şahne, Bilge (Academician Publishing Book DOI Portal, 2024)
-